HUBUNGAN ANTARA STRESS DENGAN PERILAKU MEROKOK PADA PEGAWAI NEGERI SIPIL LAKI-LAKI - Melly Rizkiani; Rita Hadi Widyastuti (Jurusan Keperawatan, Universitas Diponegoro, 2012)
Stress is a condition that could be experienced by everybody, including civil employees. Stress in civil employees could be derived from work problems, household problems, and neighborhood problems. Stress is one of many reasons for some people to smoke. Based on the result of observation and informal interview to some civil employees in Regional Secretariat Office of Brebes District, there are 86% from 173 employees that smoke. The goal of this research is to know the relationship between stress and smoking behavior among civil employees. This research used non experimental quantitative method with purposive sampling technique. Chi Square was used to analyze the relationship between two variables, used α = 0,05. This research resulted that 107 respondents were in mild stress and 2 respondents were in moderate stress. There were 55 respondents that have active smoking behavior and 54 respondents that have passive smoking behavior. Based on the analyzed result, there are no significant relationship between stress and smoking behavior among civil employees (p value = 0,252). This research could be continued by next research using qualitative method in order to get more information about smoking behavior’s factors, especially among adults.